Factor XIII and Endothelial Dysfunction in Patients with Systemic Sclerosis - Alesci, Sonja; Wahle, Matthias; Himsel, Andrea; Miesbach, Wolfgang (Hämostaseologie, 2023)
Systemic sclerosis (SSc, scleroderma) is a severe autoimmune connective tissue disease which affects the skin and internal organs. There has been evidence that coagulation factor XIII (FXIII) has a positive impact on clinical results in patients with SSc. In a single-center cohort study, we investigated the relationship between coagulation FXIII, endothelial dysfunction, and skin infection in SSc. Fifty-six patients could be included and were divided into two groups (with and without scleroderma). Markers of inflammation, coagulation, and endothelial dysfunction like C-reactive protein, leucocytes, fibrinogen, FVIII, VWF-Ag (von Willebrand factor antigen), D-dimers, and vascular endothelial growth factor were analyzed as well as MRSS (modified Rodnan skin scores) data were evaluated. Reduced daily activities were evaluated by the Scleroderma Health Assessment Questionnaire (SHAQ). There were no significant correlations between FXIII activity, MRSS, and SHAQ score. There were correlations between FXIII activity and Raynaud's phenomenon–related symptoms and a weak but not significant positive correlation with the level of pain. A significant correlation between VWF-Ag and lung-associated complaints (n = 56; p = 0.41, p < 0.0001) was found. Moreover, the study showed a correlation between VWF-Ag and MRSS (r [N = 48] = 0.4, p = 0.01), which means that higher VWF-Ag levels come along with more severe skin involvement. A trend toward a negative correlation between FXIII activity and VWF-Ag as marker of endothelial dysfunction was found (r [N = 56] = − 0.20, p = 0.15). In our cohort, there is no FXIII deficiency in patients with SSc. FXIII might have a role in improving cutaneous manifestations indirectly by means of a moderating influence on endothelial dysfunction. Further clinical evaluation is needed.
Keywords: factor XIII; transglutaminases; scleroderma; endothelial cells; von Willebrand factor